DISPUTE SETTLEMENT OF SIMULTANEOUS VILLAGE HEAD ELECTIONS BASED ON LAW NUMBER 6 OF 2014 ABOUT VILLAGES IN SELUMA REGENCY - Nurpadliya Nurpadliya; Amancik Amancik; Ardilafiza Ardilafiza (Universitas Bengkulu, 2022)
In general, the implementation of village head election does not escape from a conflict. Seluma Regency of Bengkulu Province is one of the regencies that has held simultaneous village head elections based on the Regulation of the Regent of Seluma Regency Number 26 of 2019 in conjunction with the Regulation of the Regent Number 21 of 2019 concerning Guidelines for Implementing Simultaneous Village Head Elections in the Seluma Regency Region. In the implementation of village head elections in Seluma Regency, conflicts have occurred. This study aims to analyze, to describe and to explain the disputes settlement of village head election which is conducted simultaneously in Seluma Regency in terms of Law Number 6 of 2014 about Villages. The study of this research was carried out by referring to juridical sociology view. The result showed that in Law no. 6 of 2014 concerning Villages, if there is a dispute in the implementation of Village Head Election, the Regent / Mayor is the party given the authority to resolve the dispute.